ZONA INGGRIS SEBAGAI METODE ALTERNATIF PEMBELAJARAN SPEAKING ENGLISH UNTUK ANAK SEKOLAH DASAR - arining wibowo (JURNAL ILMIAH BAHASA DAN SASTRA, 2014)
ABSTRACT This research was held in SDN Gadang 1, SDN Ciptomulyo 3 and SDN Bandungrejosari 1. This research involving English Zone participants from the aforementioned three state elementary school which taken from grade 3 to the grade 6 with 560 (five hundred and sixty) of total populations. From the amount of population we decided the most representative sample using Yaname and Slovin theory with level of precision at 10%. Then, the gained sample is filtered again using the proportional allocation theory to get the expected sample. We use these theories because of the targeted population is the heterogenic community that consist of various level grade of class. To test the hypothesis of Ha: rxy ≠ 0 which means there is significant relation and effect of English Zone to the speaking ability. In analyzing the hypothesis we use the theory of correlation of Pearson Product Moment continued to the T-Test analysis and Coefficient Determination to find the amount of variable contribution percentage. The instrument of this research taken from the score gained from the questionnaire sets. The impressive results shown in this research, English Zone contribute up to 80,5% to the speaking ability improvement (the rest is determined by other variables). Key Words: English Zone, Speaking English Ability Improvement